Attributions for success and failure in Spanish team sport players - R. González-Boto; O. Molinero; R. Martínez; S. Márquez (Asociación Española de Ciencias del Deporte, 2010)
This study examined the role of ability, effort, luck and difficulty of the task in attributions for successful and unsuccessful performances made by Spanish team sport players, and determined if differences exist between athletes at different competition levels. Participants were 143 young men (soccer: N = 64; indoor soccer: N = 37; basketball: N = 42), ages 17 to 25 years (M = 20, SD = 5). Winners perceived ability and effort as the reasons behind their success while losers made attributions mainly to luck and the difficulty of the task. Ability and effort were in the three sports the reasons given for successful outcomes at various competition levels. Difficulty of the task was the factor rated higher by those who lost competing at a national level, while luck and effort were rated higher for those who lost competing at a regional and local level. KEY WORDS: attribution, team sports. competition levels